OTSM-TRIZ Network of Problems for Evaluating the Design Skills of Engineering Students. (2015) - Becattini, Niccolò; Cascini, Gaetano; Rotini, Federico
Abstract: This paper aims at exploring the opportunities coming from the application of the OTSM-TRIZ Network of Problems as a means for mapping the design steps of engineering students coping with design problems. Both the design rationale and the design protocol can be analyzed to support the evaluation of the overall outcomes of students downwards a course on systematic design, considering both the ideas they generate and the process they follow for the ideation. The paper proposes a few improvements for the OTSM-TRIZ Network of Problems, so as to adapt it for such a purpose. Some demonstrations of the applicability of the proposed method are presented by means of two different design problems faced by groups of students having homogeneous levels of expertise and engineering skills. The results, got through a research method here detailed, highlight that the proposed approach allows the evaluators/analysts to carry out the time-demanding protocol studies with significant savings in time. Moreover, this model allows the definition of appropriate metrics to carry out homogenous and more objective evaluations among students.